# Translate sum of one-sixth of x and 2.8 into an algebraic exspression

## Answers

The answer is : 1/6x +2.8

1/6a+(-2)=-2/3. The / is used for the fraction bar.

The number would be 8.

Step-by-step explanation:

Since we have given that

The sum of one-sixth of a number and negative two is equal to negative two-thirds.

Let the number be 'x'.

So,it will be expressed as

[tex]\dfrac{1}{6}x-2=-\dfrac{2}{3}[/tex]

Now, we'll go for finding the value of 'x'.

[tex]\dfrac{x}{6}=-\dfrac{2}{3}+2\\\\\dfrac{x}{6}=\dfrac{-2+6}{3}=\dfrac{4}{3}\\\\x=\dfrac{4\times 6}{3}\\\\x=\dfrac{24}{3}\\\\x=8[/tex]

Hence, the number would be 8.

The number would be 8.

Step-by-step explanation:

Since we have given that

The sum of one-sixth of a number and negative two is equal to negative two-thirds.

Let the number be 'x'.

So,it will be expressed as

[tex]\dfrac{1}{6}x-2=-\dfrac{2}{3}[/tex]

Now, we'll go for finding the value of 'x'.

[tex]\dfrac{x}{6}=-\dfrac{2}{3}+2\\\\\dfrac{x}{6}=\dfrac{-2+6}{3}=\dfrac{4}{3}\\\\x=\dfrac{4\times 6}{3}\\\\x=\dfrac{24}{3}\\\\x=8[/tex]

Hence, the number would be 8.

[tex]\frac{1}{6}x+(-2)=-\frac{2}{3}[/tex]

Let

x------> the number

we know that

one-sixth in number is equal to [tex]\frac{1}{6}[/tex]

negative two in number is equal to [tex]-2[/tex]

negative two-thirds in number is equal to [tex]-\frac{2}{3}[/tex]

so

the complete statement

the sum of one-sixth of a number and negative two is equal to negative two-thirds

represent the equation

[tex]\frac{1}{6}x+(-2)=-\frac{2}{3}[/tex]

[tex]\frac{1}{6}x+(-2)=-\frac{2}{3}[/tex]

Step-by-step explanation:

The sum of one-sixth of a number and negative two is equal to negative two-thirds.

LEt the unknown number be x

one -sixth is [tex]\frac{1}{6}[/tex]

one-sixth of a number is [tex]\frac{1}{6}x[/tex]

The sum of one-sixth of a number and negative two

Sum represents the addition, expression becomes [tex]\frac{1}{6}x+(-2)[/tex]

Now this expression is equal to negative two-thirds. [tex]-\frac{2}{3}[/tex]

The equation becomes

[tex]\frac{1}{6}x+(-2)=-\frac{2}{3}[/tex]

It is B) 3/4a-1/2b-3

Step-by-step explanation:

I did the instructions :)

It is option 4.

Step-by-step explanation:

(1/6) n - 2 = -2/3

Adding -2 equates to -2.

It's the last one: One-sixth n minus 2 = negative two-thirds

Step-by-step explanation:

Hope this helps!!

step 2 is wrong

Step-by-step explanation:

he distributed the wrong thing